Willingness to receive the COVID-19 vaccine among HIV positive men who have sex with men in China: a cross-sectional study - Songjie Wu; Shanhui Zhu; Xumeng Yan; Yongshi Xu; Huifang Xu; Fang Yang; Zhigang Han; Yuzhou Gu; Yi Zhou; Zhengrong Yang; Huake Yang; Bo Shu; et al. (BMC, 2023)
Abstract Background People living with HIV(PLWH) are deemed more vulnerable to the SARS-CoV-2 infection than the uninfected population. Vaccination is an effective measure for COVID-19 control, yet, little knowledge exists about the willingness of men who have sex with men (MSM) living with HIV in China to be vaccinated. Methods This cross-sectional study evaluated the willingness of MSM living with HIV to receive COVID-19 vaccination in six cities of Guangdong, China, from July to September 2020. Factors associated with willingness to receive COVID-19 vaccination using multivariable logistic regression. Results In total, we recruited 944 HIV-positive MSM with a mean age of 29.2 ± 7.7 years. Of all participants, 92.4% of them were willing to receive the COVID-19 vaccine. Participants who were separated, divorced, or widowed (adjusted OR: 5.29, 95%CI: 1.02-27.48), had an annual income higher than 9,000 USD (adjusted OR: 1.70, 95%CI: 1.01-2.86), had ever taken an HIV self-test (adjusted OR: 1.78, 95%CI: 1.07-2.95), had ever disclosed sexual orientation to a doctor/nurse (adjusted OR: 3.16, 95%CI: 1.33-7.50), had ever disclosed sexual orientation to others besides their male partners (adjusted OR: 2.18, 95%CI: 1.29-3.69) were more willing to receive the vaccine. Sex with a female partner in the past six months decreased the likelihood of willingness to receive the vaccine (adjusted OR: 0.40, 95%CI: 0.17-0.95). Economic burden, worry that my health condition could not bear the risk of receiving COVID-19 vaccines, and concern that the vaccination would affect the immune status and antiretroviral therapy were the main reasons for unwillingness to receive vaccination. Conclusion Our study showed that HIV-positive MSM had a high willingness to receive the COVID-19 vaccination. Targeted interventions such as health education should be conducted among MSM with HIV infection to enhance COVID-19 vaccine uptake.